Molecularly targeted drugs for metastatic colorectal cancer - Cheng YD; Yang H; Chen GQ; Zhang ZC (Dove Medical Press, 2013)
Ying-dong Cheng, Hua Yang, Guo-qing Chen, Zhi-cao Zhang Department of General Surgery, Xinqiao Hospital, Third Military Medical University, Chongqing, People's Republic of China Abstract: The survival rate of patients with metastatic colorectal cancer (mCRC) has significantly improved with applications of molecularly targeted drugs, such as bevacizumab, and led to a substantial improvement in the overall survival rate. These drugs are capable of specifically targeting the inherent abnormal pathways in cancer cells, which are potentially less toxic than traditional nonselective chemotherapeutics. In this review, the recent clinical information about molecularly targeted therapy for mCRC is summarized, with specific focus on several of the US Food and Drug Administration-approved molecularly targeted drugs for the treatment of mCRC in the clinic. Progression-free and overall survival in patients with mCRC was improved greatly by the addition of bevacizumab and/or cetuximab to standard chemotherapy, in either first- or second-line treatment. Aflibercept has been used in combination with folinic acid (leucovorin)–fluorouracil–irinotecan (FOLFIRI) chemotherapy in mCRC patients and among patients with mCRC with wild-type KRAS, the outcomes were significantly improved by panitumumab in combination with folinic acid (leucovorin)–fluorouracil–oxaliplatin (FOLFOX) or FOLFIRI. Because of the new preliminary studies, it has been recommended that regorafenib be used with FOLFOX or FOLFIRI as first- or second-line treatment of mCRC chemotherapy. In summary, an era of new opportunities has been opened for treatment of mCRC and/or other malignancies, resulting from the discovery of new selective targeting drugs. Keywords: metastatic colorectal cancer (mCRC), antiangiogenic drug, bevacizumab, aflibercept, regorafenib, cetuximab, panitumumab, clinical trial, molecularly targeted therapy